Edukasi Perilaku Hidup Bersih Dan Sehat Dalam Rumah Tangga Terhadap Pengetahuan Kader Kesehatan - Rusdianingseh Rusdianingseh; Nety Mawarda Hatmanti; Didik Dwi Winarno (Ilmiah Institut Citra Internasional, 2022)
PHBS (Clean and Healthy Living Behavior) is very important in the household. The Covid-19 pandemic period has made us stay at home longer so that household PHBS needs to be improved, as one of the things that can improve family health. The purpose of this study was to determine the effect of household PHBS education on the level of knowledge of health cadres before and after being given education. This type of research is analytic with a quasi-experimental technique with a two-group pre-post-test approach. The target population is all active health cadres in the Kebonsari Surabaya with the criteria are adults over 21–59 years old, can read and write well, live in the Kebonsari Surabaya. The sample was 66 respondents who were divided into two groups, namely the intervention group 33 respondents and the control group 33 respondents. The instrument used was a knowledge level questionnaire that was given before and after the household PHBS education intervention. Data were analyzed using the Wilcoxon Signed Rank and Mann Whitney test with a significance level of = 0.05. The results of the different post-test experimental and control groups using the Mann Whitney test obtained a value of = 0.000 with a significance level of = 0.05, which means that there is an influence of household PHBS education through flipchart printed media on the knowledge of health cadres. The conclusion of this study is that there is an influence of household PHBS education through flipchart media on the knowledge of health cadres